An exploration of why health professionals seek to hold statutory powers in mental health services in England: considerations of the approved mental health professional role. (3rd September 2021) - Stevens, Martin; Manthorpe, Jill; Martineau, Stephen; Steils, Nicole; Norrie, Caroline
Abstract: Background: There is a shortage of Approved Mental Health Professionals (AMHPs), who are responsible for compulsory admission decisions under the Mental Health Act (MHA), 1983 . Only 5% of AMHPs are health professionals, over a decade after the role was opened to them. Aims: The research aimed to identify factors motivating and discouraging health professionals from becoming and working as AMHPs. Methods: Semi-structured interviews ( n = 52) with professionals enabled to become AMHPs by the MHA, 2007, including AMHPs; those that had not become AMHPs; and AMHP managers. Additionally, a survey of AMHP senior managers. Interviews and open-ended survey questions were analysed thematically. Results: Motivating and discouraging factors were grouped as intrinsic and extrinsic. Intrinsic motivations were: altruism; the dynamic and contained nature of the work; and fit with experience. Intrinsic discouraging factors were: damage to therapeutic relationships; the perceived clash between AMHP work and professional values. Extrinsic motivations were: career progression; and professional esteem. Extrinsic discouraging factors were: profile and reputation of the service; organisational commitment; management support; and level of remuneration. Conclusions: The research suggests that changes in organisational responsibility for running AMHP services and raising the profile of the role might help increase recruitment and retention of health professionals.